Alternative sample preparation techniques in gas chromatographic-mass spectrometric analysis of urinary androgenic steroids - Cho, Young-Dae; Choi, Man Ho (KOREAN CHEMICAL SOC, 2006)
The following study describes the gas chromatography-mass spectrometry (GC-MS) based screening and confirmation analysis of urinary androgenic steroids. Four commercially available solid-phase extraction (SPE) cartridges, Serdolit PAD-1, Sep-pak C-18, amino-propyl, and Oasis HLB, and three different extractive organic solvents, diethyl ether, methyl tert-butyl ether (MTBE), and n-pentane, were tested for sample preparation. Overall, Oasis HLB combined with MTBE extraction provided the highest recoveries in 39 of 46 total androgenic steroids examined and it showed a good extraction yield (>82.1%) for polar steroids, such as metabolites of fluoxymesterone, oxandrolone, and stanozolol, which gave a poor recovery in both n-pentane (9.2-64.3%) and diethyl ether (22.2-73.6%) extractions. All SPE sorbents tested showed potential, because they were efficient in extraction for most or selective steroids. When applied to positive urine samples based on the results obtained, the present method allowed selective and sensitive analysis for detection of urinary androgenic steroids. The experiments showed that the high-resolution MS method is clearly more efficient than the low-resolution MS technique for the detection of many urinary steroids. However, comprehensive sample clean-up procedures also might be needed especially in confirmation analysis to increase detectability.
Keywords: SOLID-PHASE EXTRACTION; ANABOLIC-STEROIDS; IDENTIFICATION; DERIVATIZATION; METABOLITES; ESTROGENS; PLASMA